Beyond the rural-urban divide cross-continental perspectives on the differentiated countryside and its regulation - Andersson, Kjell, Ph. D. (Bingley, England : Emerald Group Pub Ltd., 2009)
The rural-urban dichotomy is one of the most influential figures of thought in history, laying the foundation for academic disciplines such as rural and urban sociology. The dichotomy rests on the assumption that rural and urban areas differ fundamentally. By the mid-twentieth century, scholars had observed that many rural areas displayed a blend of rural and urban features. Since then, counterurbanisation, urban sprawl and ever-increasing flows of people, goods and ideas between rural and urban areas have blurred the distinctions even further. Attempts to create new rural-urban classification systems, whether based on factors such as population size, density or distances, have largely failed. Clearly, new classification systems must use the meaning of observed changes in rural-urban systems as their point of departure rather than simple measurements of these changes. These meanings can, despite the interdependencies of our global world, be explored only in their political, cultural and economic settings.
Introduction: beyond the rural-urban divide / Kjell Andersson ... [et al.] -- The emerging shortage of labour in forestry in a remote coniferous region: a brake on the massive use of biofuels / Olli Lehtonen and Markku Tykkyläinen -- From suburbia to rural backwater: exurban rural development in Germany / Florian Dünkmann -- Why did Russia fail in its agricultural reform? A comparative analysis of property rights in Russia and the Baltic countries / Ilkka Alanen -- The future of rural communities in Bulgaria / Eckhard Dittrich and Rumiana Jeleva -- Perceptions of agriculture's multifunctional role among rural Pennsylvanians / Martin H. Lenihan, Kathryn J. Brasier and Richard C. Stedman -- Understanding the sociocultural processes that contribute to diversity and conformity among farmers in Australia, Finland and the Netherlands / Frank Vanclay and Tiina Silvasti -- Rural-urban relations in livelihoods, governance and use of natural resources-considerations of fisheries in the Finnish Archipelago Sea region / Pekka Salmi -- Regimes and vital coalitions in rural-urban regions in the Netherlands / Ina Horlings, Pieter Tops and Julien van Ostaaijen -- Overcoming jurisdictional boundaries through stakeholder engagement and collaborative governance: lessons learned from white-tailed deer management in the U.S. / Kirsten M. Leong ... [et al.] -- Managing spatial change in the rural-urban fringe: the role of active citizenship and civil society in the Republic of Ireland / Mark Scott, Paula Russell and Declan Redmond -- Challenges of governance and land management on the exurban/wilderness frontier in the USA / Heidi E. Kretser ... [et al.] -- Knowledge integration and power relations: pathways to sustainability in Madrid / Veronica Hernandez-Jimenez and Nick Winder -- Finnish and Hungarian joint initiative in and for the information society: on the pleasure and pain of mediating in cyberspace / Sarolta Németh.
Includes bibliographical references.
Description based on print version record.
Keywords: Rural-urban relations -- Europe; Forests and forestry -- Social aspects; Forest management; Foresters; Farmers; Agriculture and state; Rural planning; Rural communities; Social Science -- Sociology -- Rural